Notice of meeting - Morgan, Betty
038-0112-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 4, GREAT SMITH STREET, LONDON, S.W.1. TELEPHONE: ABBEY 2565 January 2nd, 1939. This is to inform you that there will be a meeting of the Basque Children's Committee on January 10th, at 6.15 p.m. at 35 Marsham Street, Women's Service House, S.W.1. (in the Restaurant). It is very much hoped that you will be able to attend. BETTY MORGAN Organising Secretary. 292/946/38/112